Pneumonia Related Deaths in Sleman Based on Verbal Autopsy: an Observational Study - Stephanie Audrey Handrianto; Beta Ahlam Gizela; Djayanti Sari; Lukman Ade Chandra (Journal of Community Empowerment for Health, 2023)
Pneumonia has long been and remains one of the leading causes of death, especially among children and the elderly. Until this study was released, only the Jakarta province fulfilled the national target of pneumonia case findings. Thus, it is important to determine the characteristics and prevalence of pneumonia-related deaths in Sleman District based on verbal autopsy. This cross-sectional study used secondary data from Sleman HDSS cycles 1 to 7. The subject of this study was a person aged over 28 days who passed away due to pneumonia between 2015 and 2022 and met the criteria for sample inclusion. Fisher’s exact and Pearson’s chi-square tests were used to analyze the data. The number of subjects who died due to pneumonia was 65 subjects (33,3%), and the number of subjects who died due to other causes was 130 (66,7%). The prevalence of those who died due to pneumonia was lower than non-pneumonia death for all of the predetermined risk factors, including elderly age, male sex, low education level, high occupational risk, smoking history, alcohol consumption, asthma history, COPD history, stroke history, tuberculosis history, hospitalization history, and very thin or malnourished body with sex, occupational status & type, and nutritional status being statistically significant. The prevalence of pneumonia-related deaths in the Sleman HDSS VA population is 33,3%, with some risk factors that may affect it.